1995
DOI: 10.1111/j.1365-2265.1995.tb02040.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary‐testicular function in end‐stage non‐alcoholic liver disease before and after liver transplantation

Abstract: Hypothalamic-pituitary regulation of testicular function is impaired in end-stage non-alcoholic liver disease in proportion to the severity of underlying liver disease. Spironolactone reduces circulating testosterone but only among men with Child-Pugh B liver cirrhosis. Gonadal function improves, but is not normalized, over the first year following successful liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 37 publications
4
69
0
2
Order By: Relevance
“…In addition, the increase in SHBG leads to a stronger binding with testosterone (8,13) . In cirrhotic patients occur an increase in the peripheral conversion of androgens into estrogens (4,6,7) and a decrease in the liver depuration of estrogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the increase in SHBG leads to a stronger binding with testosterone (8,13) . In cirrhotic patients occur an increase in the peripheral conversion of androgens into estrogens (4,6,7) and a decrease in the liver depuration of estrogens.…”
Section: Resultsmentioning
confidence: 99%
“…Testosterone serum level is lower than in normal patients (5,7,9) which masks a marked fall in the non-protein-bound (biologically active) fraction of the hormone due to a large increase in the sex hormone-binding globulin (SHBG) (3,7,10) which binds testosterone with a high affinity. Most circulating testosterone is bound SHBG and only the small proportion in the free form is biologically active (8,13) . Our prospective study has shown that serum levels of FT increased in A group (MELD<18) after OLT (P<0.05) (13) and we did not find significantly changes in total testosterone serum levels after transplantation (P = 0.73).…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, patients affected with liver cirrhosis show FSH and LH levels only slightly increased, but certainly not so high as expected because of a severe lack of circulating sex hormones. As testosterone is metabolized to estrogen, a long duration of hypogonadism in men is often associated with a reduction in circulating estrogens, and consequent reduced bone turnover, with decreased osteosynthesis [7]. Since these endocrine alterations described above play a heavy clinical role in male, it is clear that most studies on this aspect have been conducted in cirrhotic males.…”
Section: Pathophysiology Of Osteoporosis In Chronic Liver Diseasesmentioning
confidence: 99%
“…The production of testosterone by cirrhotic individuals is, on average, 25% of that found in normal individuals (3). Low levels of this hormone are already noted even in ChildPugh A cirrhotic patients, and the decline is directly proportional to the degree of liver failure (4,5).…”
Section: Introductionmentioning
confidence: 99%